Development of Nutritionally Balanced Ready-to-Eat Meals in Retort Pouches for Elderly Individuals with Dysphagia and Chewing Difficulties. - MAISONT, SUCHADA; SANGSIRIMONGKOLYING, RATSAMEE; KULPRASUTIDILOK, AKUA; CHOKBORIBAL, JAROENPORN; SAMUTSRI, WISUTTHANA (Current Research in Nutrition & Food Science, 2025)
This study aimed to develop and evaluate ready-to-eat mixed rice and fish curry products suitable for elderly individuals with chewing and swallowing difficulties. Jasmine rice and Riceberry were combined in varying ratios (4:0, 3:1, 2:2, and 1:3) and subjected to thermal sterilization at 116°C for 35 min (Fo = 6). Steamed fish curry curd was formulated with varying fish-to-egg ratios (42:8, 40:10, 38:12, and 36:14%) and sterilized at 116°C for 40 min (Fo = 6). The International Dysphagia Diet Standardization Initiative (IDDSI) Fork Pressure Test confirmed the suitability of the products for individuals with dysphagia. pH analysis, protein content via the Kjeldahl method, and syneresis analysis were performed to ensure product stability. Color measurement and texture profile analysis (hardness, adhesiveness, cohesiveness, gumminess, chewiness) were conducted. Sensory evaluation with 32 elderly participants assessed acceptability based on a 7-point hedonic scale. Statistical analysis showed significant differences (P ≤ 0.05) among the various formulations, with optimal texture and sensory properties in the 1:3 rice mixture and 38:12 fish-to-egg ratio. Microbiological analysis confirmed compliance with food safety regulations. The findings support the potential of retorted mixed rice and fish curry as a nutritious, accessible meal option for dysphagia elderly individuals.